Chrysophanol Inhibits the Progression of Diabetic Nephropathy via Inactivation of TGF-β Pathway - Guo C; Wang Y; Piao Y; Rao X; Yin D (Dove Medical Press, 2020)
Chuan Guo,1,2 Yarong Wang,1 Yuanlin Piao,1 Xiangrong Rao,2 Dehai Yin1 1Department of Traditional Chinese Medicine, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Science, Beijing 100730, People’s Republic of China; 2Department of Nephropathy, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing 100053, People’s Republic of ChinaCorrespondence: Dehai YinDepartment of Traditional Chinese Medicine, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Science, No. 1 Shuaifuyuan, Beijing 100730, People’s Republic of ChinaEmail yindehai123@126.comBackground: Diabetic nephropathy (DN) is a common form of diabetic complication which threatens the health of patients with diabetes. It has been reported that chrysophanol (CHR) can alleviate the progression of diabetes; however, the role of CHR in DN remains unclear.Methods: To mimic DN in vitro, human podocytes (AB8/13 cells) were treated with high glucose (HG). Meanwhile, Western blot was performed to detect protein expressions. CCK-8 assay was used to test cell viability and cell proliferation was detected by Ki-67 staining. In addition, flow cytometry was performed to investigate cell apoptosis and cycle and cell migration was tested by transwell assay. Moreover, in vivo model of DN was established to detect the effect of CHR on DN in vivo.Results: HG-induced AB8/13 cell growth inhibition was significantly rescued by CHR. In addition, HG notably promoted the migration of AB8/13 cells, while this phenomenon was obviously reversed by CHR. Moreover, CHR inhibited the progression of DN via inactivation of TGF-β/EMT axis. Furthermore, CHR alleviated the symptom of DN in vivo.Conclusion: CHR significantly alleviated the progression of DN via inactivation of TGF-β/EMT signaling in vitro and in vivo. Our findings were helpful to uncover the mechanism by which CHR regulates DN, as well as inspire the development of novel therapy against DN.Keywords: diabetic nephropathy, chrysophanol, TGF-β, EMT